Enhanced antibacterial testing and latent fingerprint detection using dichlorofluorescein-doped carbon dots - Aphinya Thinthasit; Elvaro Islami Muryadi; Syamsun Jaya; David Nugroho; Saksit Chanthai; Rachadaporn Benchawattananon (Journal of Saudi Chemical Society)
This research presents an innovative multifunctional reagent consisting of dichlorofluorescein-doped carbon dots (CDs-DC) generated from fresh coconut water by a hydrothermal method. This work’s innovation resides in the simultaneous application of CDs-DC for latent fingerprint detection on nonporous surfaces and improved antibacterial efficacy. The incorporation of dichlorofluorescein into the CDs matrix enhances photoluminescent characteristics and improves antibacterial effectiveness against Gram-positive and Gram-negative bacteria (Escherichia coli, Serratia marcescens, Bacillus megaterium, Staphylococcus aureus). The addition of a starch matrix significantly strengthened this combination, enhancing the adherence and recognition of complex fingerprint patterns under UV light. Furthermore, the CDs-DC demonstrated significant reactive oxygen species (ROS) production, enhancing their antibacterial efficacy. This dual-functional device represents a notable progression in forensic science and antibacterial technology, establishing itself as a sustainable and highly efficient instrument for these purposes.